Research environments: can the cloud supplement bricks and mortar?. Issue 9 (21st August 2018) - Varpio, Lara; Frank, Jason; Sherbino, Jonathan; Snell, Linda S; Young, Meredith
Abstract : While local research environments significantly impact individuals' abilities to engage in scholarly activities, we contend that health professions education scholars are increasingly mobilizing virtual spaces and resources to further their research endeavors.